Environmental philosophy the art of life in a world of limits - Leonard, Liam. (Bingley, U.K. : Emerald, 2013)
Humankind has long considered the relationship it holds with nature to be both a blessing and a challenge. The onset of climate change has brought a new impetus to this relationship. This volume of Advances in Sustainability and Environmental Justice will examine environmental philosophy from a number of viewpoints. Each contributor has a unique perspective on the interaction and engagement between humanity and the rest of nature, from the technological to the philosophical. Environmental Philosophy: the Art of Life in a World of Limits provides a series of interesting studies on humanitys place in the world, and the impact this is having on the planet. The book poses the question as to whether life can be lived in harmony with nature, and what limits can be achieved in the impact such life has on the world around us.
Introduction / Liam Leonard -- MacIntyre and Havel as green political thinkers : unreasonable thinking in turbulent times / John Barry -- The transition to green lifestyles based on voluntary simplicity : the difficult road towards enjoyable, graceful and sustainable lifestyles / Marius de Geus -- The politics of global warming (1) : climate science and scepticism / Graham Parkes -- The politics of global warming (2) : two obstacles to circumvent / Graham Parkes -- A call for a new political economy of attention : mindfulness as a new commons / Peter Doran -- Territory in a world of limits : exploring claims to oil and ice / Cara Nine -- Mandatory non-anthropocentrism : the political unrealism of making metaethical demands in environmental ethics / Jason Dockstader -- Irish ruins ancient and new : ghost estates, megaliths and human relations with the rest of nature / Geoff Berry -- Walking respectfully on the earth : a problem for deep ecology / Thomas Duddy.
Print version record
Keywords: Nature -- Environmental Conservation & Protection; Science -- Environmental Science; Political Science -- Public Policy -- Environmental Policy; Environmentalist thought & ideology; Social impact of environmental issues; Environmental sciences -- Philosophy